Verbal Evidence of Task-related Strategies in EFL: Children and Adult Interactions - Azpilicueta-Martínez, Raúl (International Journal of English Studies, 2020)
The benefits of task-based interaction in Second Language Learning (SLL) have been made increasingly evident in the literature. However, unlike adult studies, only recently has interaction research on EFL children grown in popularity. Most children-based research has focused primarily on Negotiation of Meaning, while other age-related aspects, including a more comprehensive analysis of how adults and children perform and resolve tasks, remain relatively unexplored. This paper addresses this gap by analysing the similarities and differences in the task-related strategies of twenty children aged 8 and 9 and fourteen adult L1-Spanish EFL learners at low levels of competence in paired interaction. Results provide evidence of clear age-related differences, as adults were more consistent and approached the task in a more predictable and efficient fashion. Findings also point to task repetition as a key factor leading to a more successful performance in both groups, even more markedly in the case of children.